Bridging Career Guidance and Industry Readiness: A Systematic Literature Review of Vocational High School Students in Fashion Design Education - Yuyun Dwi Sayekti; Tuwoso (Eduscape : Journal of Education Insight, 2026)
The rapid transformation of the fashion industry, driven by digitalization and sustainability transitions, has increased the complexity of career pathways and competency demands for vocational graduates. However, a persistent mismatch remains between the skills developed in vocational education and those required by the industry. This study aims to systematically examine the career guidance needs of vocational high school students in fashion design education and their relation to industry readiness. A Systematic Literature Review (SLR) was conducted following PRISMA guidelines. The review included 20 peer-reviewed articles published between 2019 and 2026 and indexed in Scopus and Web of Science. This timeframe was selected to capture recent developments related to digital transformation and sustainability trends in vocational and fashion education. Data were analyzed using thematic synthesis to identify recurring themes, patterns, and research gaps. The findings indicate that career guidance needs extend beyond informational support, encompassing self-awareness, career decision-making skills, employability competencies, industry exposure, and opportunity creation. Among these, career adaptability and employability emerge as key factors associated with students’ readiness for the labor market. The review also reveals ongoing gaps in curriculum relevance, soft skills development, and alignment with industry practices. The study suggests that more effective career guidance in vocational fashion education involves integrating work-based learning, digital tools, industry partnerships, and entrepreneurial orientation. Rather than proposing a definitive model, this review highlights the need for a more integrated and competency-based approach to career guidance. These findings contribute to the ongoing discussion on strengthening the role of career guidance in enhancing industry readiness within vocational education contexts.